Reading performance with different correlated colour temperature among presbyopia / Nor Shazana Mokhtar - Mokhtar, Nor Shazana (Faculty of Health Sciences, 2015)
Introduction: Correlated colour temperature (CCT) is important characteristic of lights to be considered regarding to human perception. Good selection of lighting can improved the reading performance among presbyopia. Objective: The aim of this study is to determine the effect of warm white light (WWL) (CCT = 2856 K), cool white light (CWL) (CCT = 4100 K) and artificial daylight (DL)(CCT = 6500 K) on the near reading performance among presbyopia. Methodology: This study involved fourteen presbyopia subjects aged between 35 to 65 years old (3 male, 11 female), with their mean value of distance refractive power was -0.75D and mean value of addition power was +2.00D. GTI ColorMatcher light booth consist of three sources of light and two types of UiTM Mrw reading charts had been used to evaluate reading performance among presbyopia. Result: One-way repeated-measure ANOVA showed that the reading performance were statistically significant increase CWL to DL and WWL to DL [12.68 (95% CI, 0.84 to 24.51) wpm, p< 0.05] and [13.33(95% CI, 1.73 to 24.92) wpm, p<0.05]. However there were no significant difference in term of reading accuracy between CWL, WWL, and DL. Conclusion: The instillation of high CCT could give benefit in increasing the reading performance and reading accuracy among presbyopia.